CONCEPT OF UDAVARTA (PRIMARY/SPASMODIC DYSMENORRHOEA) – AN AYURVEDIC PERSPECTIVE (International Journal of Ayurveda and Pharma Research, 2021)
Many women are familiar with the experience of spasmodic dysmenorrhoea, one of the commonest gynaecological conditions that affects the quality of life of many in their reproductive years.This condition manifested as painful menstruation, is the most frequently encountered gynaecological complaint and it can be included under Udavartha yonivyapat, caused by Apana vata vaigunya described in Ayurvedic classics. Nidana samprapthi and Rupa of Udavartha yonivyapat can well explain the etiopathogenesis and clinical features of Spasmodic dysmenorrhoea. “Arthave sa vimukthe tu tat kshanam labhate sukham” mentioned by Acharya Charaka substantiate the close similarity of Udavarta with Spasmodic dysmenorrhoea. Vegodavarthana leading to Pratiloma gati of Apana vata and rajas is the pathology behind Udavartha yonivyapath. So treatment should aim at the relief of pain by normalising the direction of menstrual flow which in turn is by normalising the vitiated Apana vayu. The present paper is aimed at incorporating all the references regarding Udavartha including Nidana panchakas from Ayurvedic classics and tried to give an Ayurvedic view to the concept and postulated theories on spasmodic dysmenorrhoea.